A Non-imaging High Throughput Approach to Chemical Library Screening at the Unmodified Adenosine-A3 Receptor in Living Cells - Arruda, Maria Augusta; Stoddart, Leigh A.; Gherbi, Karolina; Briddon, Stephen J.; Kellam, Barrie; Hill, Stephen J. (Frontiers in Pharmacology, 2017)
Recent advances in fluorescent ligand technology have enabled the study of GPCRs in their native environment without the need for genetic modification such as addition of N-terminal fluorescent or bioluminescent tags. Here, we have used a non-imaging plate reader (PHERAstar FS) to monitor the binding of fluorescent ligands to the human adenosine-A3 receptor (A3AR; CA200645 and AV039), stably expressed in CHO-K1 cells. To verify that this method was suitable for the study of other GPCRs, assays at the human adenosine-A1 receptor, and β1 and β2 adrenoceptors (β1AR and β2AR; BODIPY-TMR-CGP-12177) were also carried out. Affinity values determined for the binding of the fluorescent ligands CA200645 and AV039 to A3AR for a range of classical adenosine receptor antagonists were consistent with A3AR pharmacology and correlated well (R2=0.94) with equivalent data obtained using a confocal imaging plate reader (ImageXpress Ultra). The binding of BODIPY-TMR-CGP-12177 to the β1AR was potently inhibited by low concentrations of the 1-selective antagonist CGP 20712A (pKi 9.68) but not by the β2- selective antagonist ICI 118551(pKi 7.40). Furthermore, in experiments conducted in CHO K1 cells expressing the 2AR this affinity order was reversed with ICI 118551 showing the highest affinity (pKi 8.73) and CGP20712A (pKi 5.68) the lowest affinity. To determine whether the faster data acquisition of the non-imaging plate reader (~3 min per 96-well plate) was suitable for high throughput screening, we screened the LOPAC library for inhibitors of the binding of CA200645 to the A3AR. From the initial 1263 compounds evaluated, 67 hits (defined as those that inhibited the total binding of 25nM CA200645 by ≥40%) were identified. All compounds within the library that have medium to high affinity for the A3AR (pKi ≥6) were successfully identified. We found three novel compounds in the library that displayed unexpected sub-micromolar affinity for the A3AR. These were K114 (pKi 6.43), retinoic acid p-hydroxyanilide (pKi 6.13) and SU 6556 (pKi 6.17). Molecular docking of these latter three LOPAC library members provided a plausible set of binding poses within the vicinity of the established orthosteric A3AR binding pocket. A plate reader based library screening at an untagged receptor is therefore